Asymmetric SIS membranes specifically loaded with exosomes through the modification of engineered recombinant peptides for guide bone regeneration. (1st March 2022) - Ma, Shiqing; Zhao, Yifan; Yang, Yilin; Mu, Yuzhu; Zhang, Lei; Wu, Jinzhe; Li, Rui; Bian, Xiaowei; Wei, Pengfei; Jing, Wei; Zhao, Bo; Liu, Zihao; et al.
Abstract: Guided bone regeneration (GBR) technology is an effective method for reconstructing bone defects, and barrier membranes are widely used in this process. The objective of this study was to develop a novel asymmetric SIS (small intestinal submucosa) membrane and modify the membrane with exosomes and engineered recombinant peptides. The asymmetric SIS membrane was developed with liquid nitrogen quencher. The engineered recombinant peptides were designed by connecting collagen binding peptides with the exosomal capture peptide CP05 via linker. In vitro experiments demonstrated that the engineered recombinant peptides contributed to promoting the positive effect of exosomes on the osteogenic differentiation of BMSCs. Further mechanistic studies confirmed that the PI3K/Akt signaling pathway is critical in the exosome-induced osteogenic differentiation of BMSCs. Moreover, the asymmetric SIS membrane combining engineered recombinant peptides and exosomes could reconstruct bone defects effectively within 12 weeks. Therefore, the membrane developed in this study has the potential to repair bone defects. Highlights: The asymmetric SIS membrane was developed using liquid nitrogen quencher. Engineered recombinant peptides were designed by connecting collagen binding peptides with CP05. SIS–P1P2-EXO membranes could reconstruct bone defects effectively within 12 weeks.